Effect of smoking on periodontal therapy and subgingival flora after treatment - WANG Ning-xun; ZHANG Zhi-juan; YIN Xiao-jian (Zhongguo linchuang yanjiu, 2022)
Objective To investigate the influence of smoking on subgingival flora after periodontitis treatment through microbiological experiments. Methods Fifty-nine patients with periodontitis who completed periodontal treatment in the Department of Stomatology of Nanjing Jiangbei Hospital from 2019 to 2021 were selected and divided into smoking group(30 patients) and non-smoking group(29 patients). The clinical samples of patients's periodontal pockets before and after treatment were collected for detection of Actinobacillus (Aa), Porphyromonas gingivalis (Pg), Plasmobacterium intermedius (PI), Bacteroides forsythiae (Bf), Fusobacterium nucleatum (Fn) and Streptococcus minimus (Pm). Results After treatment, the bleeding index and periodontal attachment of the smoking group were better than those before treatment, while the plaque area index, bleeding index, periodontal pocket depth and periodontal attachment of the non-smoking group were better than those before treatment, and the plaque area index, periodontal pocket depth and periodontal attachment of the non-smoking group were better than those of the smoking group, with statistically significant differences(P＜0.05). After treatment, the positive rate of Pg and Pi in the smoking group was lower than that before treatment, the positive rate of Aa, Pg, Pi, Bf, Fn and Pm in the non-smoking group was lower than that before treatment, and the positive rate of Pg, Bf, Fn and Pm in the non-smoking group was lower than that in the smoking group, with statistically significant differences(P＜0.05). Conclusion Compared with smokers, non-smokers have better periodontal attachment recovery and lower detection rate of periodontal bacteria after periodontal treatment.